Unilateral Lung Agenesis: A Case Series and Review of Literature - Jennifer Weber; Sunil Kumar Sati; Vijender Rao Karody (Thieme Medical Publishers, Inc., 2023)
Unilateral lung agenesis is a rare congenital abnormality that typically presents with respiratory distress after birth. Prognostic factors include the side of the lung affected along with the presence or absence of other congenital abnormalities. Prenatal imaging can make the diagnosis that can assist the healthcare team in preparing to care for the neonate, as well as set expectations for the family. In this case series, we describe three cases of unilateral lung agenesis, two infants with right lung agenesis, and one with the left. We describe their presentation, provide a brief clinical course, and discuss outcomes.